You are on page 1of 30

# Economic Rationality Qua Expected Utility Theory

## The math behind it via Jensens inequality

x is a random variable with realizations x1 and x2, x1 < x2. u is the utility function. u is increasing and strictly concave. p = prob{x = x1}, 1 p = prob{x = x2} Model Setup

x is a random variable with realizations x1 and x2, x1 < x2. u is the utility function. u is increasing and strictly concave. p = prob{x = x1}, 1 p = prob{x = x2} Model Setup

x is a random variable with realizations x1 and x2, x1 < x2. u is the utility function. u is increasing and strictly concave. p = prob{x = x1}, 1 p = prob{x = x2} Model Setup

## If u is strictly concave and 0 < p < 1, then u(E(x)) > E(u(x)).

Jensens Inequality Derivation for the two-point support case

## If u is strictly concave and 0 < p < 1, then u(E(x)) > E(u(x)).

Jensens Inequality Derivation for the two-point support case

## If u is strictly concave and 0 < p < 1, then u(E(x)) > E(u(x)).

Jensens Inequality Derivation for the two-point support case

Looking at it Graphically

## Base and Height

Larger D: Base = x2 - x1 Height = u(x2) u(x1). Smaller D: Base = E(x) - x1 Height = ? E(x) - x1 = px1 + (1 p)x2 x1 = (1 p)(x2 x1).

## A little bit of algebra

Larger D: Base = x2 - x1 Height = u(x2) u(x1). Smaller D: Base = (1 p)(x2 x1). Smaller D: Height = (1 p)[u(x2) u(x1)].

Conclusion

More Algebra

More Algebra

## u(x1) + (1 p)[u(x2) u(x1)] = u(x1) - (1 p)u(x1) + (1 p)u(x2) = pu(x1) + (1 p)u(x2) = E(u(x))

More Algebra

Justification of Labeling

Constant Absolute Risk Aversion Constant Relative Risk Aversion Quadratic Utility

## Three Functional Forms for u

Constant Absolute Risk Aversion Constant Relative Risk Aversion Quadratic Utility

## Three Functional Forms for u

Constant Absolute Risk Aversion Constant Relative Risk Aversion Quadratic Utility

## Three Functional Forms for u

u(x) = -ke-gx + c; k, g, and c constants; k, g > 0. u(x) = gke-gx > 0, u(x) = -g2ke-gx < 0. -u(x)/u(x) = g.

## Constant Absolute Risk Aversion

u(x) = -ke-gx + c; k, g, and c constants; k, g > 0. u(x) = gke-gx > 0, u(x) = -g2ke-gx < 0. -u(x)/u(x) = g.

## Constant Absolute Risk Aversion

u(x) = -ke-gx + c; k, g, and c constants; k, g > 0. u(x) = gke-gx > 0, u(x) = -g2ke-gx < 0. -u(x)/u(x) = g.

## Constant Absolute Risk Aversion

u(x) = kxa + c; k, a, and c constants; k > 0, 0 < a < 1. u(x) = akxa-1 > 0, u(x) = a(a-1)kxa-2 < 0. -xu(x)/u(x) = 1 - a.

## Constant Relative Risk Aversion

u(x) = kxa + c; k, a, and c constants; k > 0, 0 < a < 1. u(x) = akxa-1 > 0, u(x) = a(a-1)kxa-2 < 0. -xu(x)/u(x) = 1 - a.

## Constant Relative Risk Aversion

u(x) = kxa + c; k, a, and c constants; k > 0, 0 < a < 1. u(x) = akxa-1 > 0, u(x) = a(a-1)kxa-2 < 0. -xu(x)/u(x) = 1 - a.

## Constant Relative Risk Aversion

u(x) = -ax2 + bx + c; a, b, and c constants; a, b > 0. u(x) = -2ax + b > 0 if x < b/2a, u(x) = -2a < 0. E(u(x)) = -aE(x2) + bm + c = -a(s2 + m2) + bm + c.